First fossil skull of chelus (Pleurodira: Chelidae, matamata turtle): from the early miocene of Colombia (2015)
Here we describe the first fossil skull so far known for the turtle genus Chelus from the early Miocene (~ 16 m.y.), Castilletes Formation, Alta Guajira Peninsula, Cocinetas basin, Colombia. The skull is partially preserved, including most of the basicranium (pteygoid-bassioccipital bones) and the roof elements including the parietal, pterygoid and portions of the squamosal, supraoccipital and the most dorsal quadrate. The skull is preserved in three dimensions, without evidence of crushing, allowing the observation of the internal braincase morphology using microcomputer tomography. Comparisons with the skull of the only extant species for the genus Chelus fimbriata (Matamata turtle) allow us to conclude that for the last 16 million years the morphology of the skull for this genus has remained almost unvarying, with only a slightly higher compression of the most anterior braincase exhibited by the extant species. Due to its fragmentary condition, a more refined identification beyond the genus (Chelus sp.) is not possible; however, the overall skull design indicates that the fossil species could also have had the same ecological and dietary adaptations as its extant relative.